Growth rate and survival of hard coral Acropora sp. in turbid waters of the Spermonde Islands, South Sulawesi, Indonesia - DEDI PARENDEN; CHAIR RANI; JAMALUDDIN JOMPA; WILLEM RENEMA; JEREMIAS RUMALA TUHUMENA (Society for Indonesian Biodiversity, 2024)
Abstract. Parenden D, Rani C, Jompa J, Renema W, Tuhumena JR. 2024. Growth rate and survival of hard coral Acropora sp. in turbid waters of the Spermonde Islands, South Sulawesi, Indonesia. Biodiversitas 25: 3208-3216. Coral reef recovery is often done by utilizing coral reproduction or coral transplantation. The aim of this study was to observe the rate of coral growth, coral survival in turbid waters, and its relationship to environmental parameters. The method used is spider webs with coral fragments. The results of hard coral restoration research of the genus Acropora in turbid waters using web spider transplantation media showed that the growth rate of Acropora donei Veron & Wallace, 1984 and Acropora millepora (Ehrenberg, 1834) in length was faster than in width. In contrast, Acropora muricate Linnaeus, 1758 corals grew in height and width equally. The observation from the three research stations revealed the growth rate is better at station three than at other stations. Coral survival of A. donei ranged from 69-86%, A. muricata ranged from 71-77%, and A. millepora ranged from 75-83%. Environmental parameters that characterize station 1 are high nitrate and phosphate, and station 2 is temperature, power of hydrogen (pH), low salinity, and high total dissolved solid. Station 3 was characterized by low chlorophyll, conductivity, and dissolved oxygen parameters. The biplot graph revealed that it is suspected that turbidity and total suspended solid are parameters that characterize the three research stations. Based on the regression analysis results, it can be seen that the water turbidity parameter does not significantly affect coral growth with p>0.05.